How to define and build an effective cyber threat intelligence capability - Dalziel, Henry (Elsevier, 2015)
One of the most important concepts in the world of information security today is defining and building an effective cyber threat intelligence capability. Covers the keys to successful implementation and discusses who are the right vendors, partners, or employees to build, staff, and run your cyber threat intelligence program